Методологічні підходи до комплексної оцінки рівня природно-техногенної небезпеки регіонів України - Обиход, Г.О.; Щуліпенко, В.Є. (Економіка природокористування і охорони довкілля, 2013)
Розкрито доцільність запровадження комплексної оцінки природно-техногенної небезпеки, визначено її аналітичну базу та розраховано інтегральний показник за наведеною методикою. Обґрунтовано пріоритетні напрями діяльності щодо гарантування безпеки, засновані на результатах комплексних оцінок природно-техногенного навантаження. The efficiency of the use of complex analytic assessments to determine the level of natural and industrial safety areas of different rank. Analysis of the various authors' approach has revealed that there is a need to improve both analytical basis of such calculations, and methods of their implementation. During the implementation of this goal has been made a comprehensive assessment of the level of security of the regions of Ukraine, which allowed us to determine the overall level of risk areas and the livelihoods of people, and predetermined conclusions about the importance of using assessment results for the prediction and prevention of emergencies. Among the main causes of a threat in the future we highlight: the persistence of significant scale of the factors of natural hazards and increase the dynamics of socially dangerous diseases, human pressures, complex technical state of production facilities, weak enforcement technology standards and other regions of the groups we identified significant differences in threat due to several reasons, namely the presence of a developed industry and potentially dangerous industries, distribution of natural hazards (geological, meteorological, hydrological), level of medical and biological hazards. Found that the main strategic goal of the state policy in the field of population and territories from emergency situations is to achieve a guaranteed level of security of the individual, society and the state, corresponding to the level of developed countries and the criteria of acceptable risk. For this purpose it is necessary to develop a system of preventive organizational and economic measures that meet the strategy for Ukraine. Justified priority areas of security, based on the results of comprehensive assessments of natural and anthropogenic impact.